Early expression of capsule during Bacillus anthracis germination - Fastenackels, Solène; Mock, Michèle; Tournier, Jean-Nicolas; Goossens, Pierre L. (Research in microbiology, 2023)
Bacillus anthracis is a spore-forming bacterium that produces two major virulence factors, a tripartite toxin with two enzymatic toxic activities and a pseudo-proteic capsule. One of the main described functions of the poly-gamma-D-glutamate capsule is to enable B. anthracis bacilli to escape phagocytosis. Thus, kinetics of expression of the capsule filaments at the surface of the emerging bacillus during germination is an important step for the protection of the nascent bacilli. In this study, through immunofluorescence and electron microscopic approaches, we show the emergence of the capsule through a significant surface of the exosporium in the vast majority of the germinating spores, with co-detection of BclA and capsular material. This suggests that, due to an early capsule expression, the extracellular life of B. anthracis might occur earlier than previously thought, once germination is triggered. This raises the prospect that an anti-capsular vaccine may play a protective role at the initial stage of infection by opsonisation of the nascent encapsulated bacilli before their emergence from the exosporium.